Current Research and Development Trend of 5G Network Technologies - Hucheng Wang; Hui Xu; Zhimi Cheng; Ke Wang (Dianxin kexue)
The challenges for mobile communication network raised by new requirements in 5G were analyzed, and then the necessity of researching 5G network technologies was explained. After that, the research situation of global research organizations was introduced, such as NGMN, 5GPPP, IMT-2020 and so on, regarding 5G network technologies, moreover, the standardization status of global standards development organizations on 5G network technologies were introduced. According to the analysis on new requirements and new challenges in 5G network, and current research of 5G network technologies, the development trend of 5G network technologies was predicted and some specific network technologies for the future network were provided. At last, the development of 5G network was concluded and forecasted.